Dynastic Politics in the Context of Modern Indonesian Law: A Comparative Study of Classical Fiqh Siyasah and Contemporary Constitutionalism - Adnan Adnan (Jurnal Syariah dan Hukum Komparatif, 2026)
This study explores the phenomenon of political dynasties in modern Indonesian constitutional law through a comparative analysis with classical Islamic political thought (fiqh siyasah). In recent years, Indonesia has witnessed the rise of political dynasties, notably exemplified by President Joko Widodo’s familial political trajectory. Such developments have prompted critical debates regarding democratic integrity and the rule of law. This study analyzes the legal and normative frameworks that govern political dynasties in Indonesia, highlighting the tension between democratic ideals and practices that may undermine meritocracy and institutional accountability. Drawing from classical Islamic political jurisprudence, the paper examines the shift from consultative leadership (shura) to dynastic rule during the Umayyad period under Muawiyah ibn Abi Sufyan. It then compares this historical transformation with contemporary Indonesian political dynamics, where constitutional mechanisms are sometimes interpreted to accommodate dynastic interests. The study argues that while classical Islamic governance recognized the practical necessity of hereditary rule in certain contexts, contemporary constitutionalism demands adherence to democratic principles and legal equity. Through this comparative lens, the paper offers a nuanced critique of dynastic politics and proposes reforms to strengthen Indonesia’s democratic resilience and legal order. The findings contribute to broader discourses on political ethics, legal reform, and Islamic constitutional thought in democratic societies.